1983
DOI: 10.1901/jeab.1983.39-251
|View full text |Cite
|
Sign up to set email alerts
|

Autoshaped Responding: A Baseline for Studying Stimulus Preference

Abstract: In an autoshaping procedure with pigeons, trials consisted of the illumination of two keys, each with a different color, and then a response-independent feeder operation. Over successive conditions, all key-color pairs were arranged from the set of amber, red, green, and blue lamps. During sessions with a given pair, the left-right configuration of the colors varied irregularly, and the two colors alternated in illuminating the feeder. With one red and one green key, for example, red appeared sometimes on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1

Year Published

1988
1988
1989
1989

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 24 publications
(21 reference statements)
0
9
1
Order By: Relevance
“…The results of Experiments 1, 2, and 2a suggested that color preference as described by Catania et al (1983) may have been controlled by the intensity of the stimuli rather than by the chromatic properties. We obtained samples of three of the original color stimuli used by Catania et al and measured their respective intensities, which were 44,000 lx for red, 6,875 lx for green, and 5,500 lx for blue.…”
Section: Experiments 2a Methodsmentioning
confidence: 88%
See 4 more Smart Citations
“…The results of Experiments 1, 2, and 2a suggested that color preference as described by Catania et al (1983) may have been controlled by the intensity of the stimuli rather than by the chromatic properties. We obtained samples of three of the original color stimuli used by Catania et al and measured their respective intensities, which were 44,000 lx for red, 6,875 lx for green, and 5,500 lx for blue.…”
Section: Experiments 2a Methodsmentioning
confidence: 88%
“…In Experiments 1 and 2, each peck was followed by reinforcement, whereas in Catania et al (1983) grain was delivered in a strictly response-independent arrangement that was, in effect, an autoshaping procedure similar to that of Brown and Jenkins (1968). The importance of this difference between Experiments 1 and 2 and those of Catania et al was assessed in Experiment 3, in which we used a response-independent reinforcement procedure.…”
Section: Experiments 2a Methodsmentioning
confidence: 99%
See 3 more Smart Citations